MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN EDUCATIONAL SERVICES FOR STUDENTS WITH HEARING IMPAIRMENTS AT SLB NEGERI CICENDO BANDUNG - Adzania, Nesa Halimah; Mastiani, Emay (Jurnal Konseling Pendidikan Islam, 2025)
Education is the right of every citizen, including people with disabilities. Deaf students need special educational services supported by appropriate facilities and infrastructure, such as hearing aids, visual media, and teachers who master sign language, so that they can be needed to support the learning process of deaf students optimally., The purpose of this study is to obtain an overview and analysis of the Management of Facilities and Infrastructure Management in Educational Services for Deaf Students at SLB Negeri Cicendo Bandung, by is studied based on the theory of Deming. This study uses a qualitative descriptive approach, with data collection techniques including observation studies, interviews, and documentation studies. The results of the research at SLB Negeri Cicendo Bandung, Planning is designed in a structured manner to support inclusive and vocational learning for students with hearing disabilities. This facility aims to meet the needs of learning as a whole and carry out the legal mandate related to special education, Implementation is carried out systematically, planned, and collaboratively, by involving various parties to meet the needs of students with hearing disabilities, Examinations are carried out regularly and participatory to ensure that facilities are always feasible, safe, and support the learning of students with hearing disabilities, Follow-up is carried out systematically and Collaborative by involving relevant parties to plan, budget, and improve facilities according to priorities, The main obstacles are limited hearing aids and inadequate visual learning media, Routine training solutions for teachers and staff to optimize the use of facilities, procurement and maintenance of hearing aids in a planned manner, and establish partnerships with relevant institutions for resource support.